Genetic knockdown and pharmacological inhibition of parasite multidrug resistance transporters disrupts egg production in Schistosoma mansoni. - Ravi S Kasinathan; William M Morgan; Robert M Greenberg (Public Library of Science (PLoS), 2011)
P-glycoprotein (Pgp) and multidrug resistance-associated proteins (MRPs) are ATP-dependent transporters involved in efflux of toxins and xenobiotics from cells. When overexpressed, these transporters can mediate multidrug resistance (MDR) in mammalian cells, and changes in Pgp expression and sequence are associated with drug resistance in helminths. In addition to the role they play in drug efflux, MDR transporters are essential components of normal cellular physiology, and targeting them may prove a useful strategy for development of new therapeutics or of compounds that enhance the efficacy of current anthelmintics. We previously showed that expression of Schistosoma mansoni MDR transporters increases in response to praziquantel (PZQ), the current drug of choice against schistosomiasis, and that reduced PZQ sensitivity correlates with higher levels of these parasite transporters. We have also shown that PZQ inhibits transport by SMDR2, a Pgp orthologue from S. mansoni, and that PZQ is a likely substrate of SMDR2. Here, we examine the physiological roles of SMDR2 and SmMRP1 (the S. mansoni orthologue of MRP1) in S. mansoni adults, using RNAi to knock down expression, and pharmacological agents to inhibit transporter function. We find that both types of treatments disrupt parasite egg deposition by worms in culture. Furthermore, administration of different MDR inhibitors to S. mansoni-infected mice results in a reduction in egg burden in host liver. These schistosome MDR transporters therefore appear to play essential roles in parasite egg production, and can be targeted genetically and pharmacologically. Since eggs are responsible for the major pathophysiological consequences of schistosomiasis, and since they are also the agents for transmission of the disease, these results suggest a potential strategy for reducing disease pathology and spread.